Preparation method of hard carbon sodium battery negative electrode material

By using asphalt as raw material, surface oxidation and resin cross-linking treatment, a high-performance hard carbon sodium electro-negative electrode material is formed, which solves the problems of high cost and performance disadvantages of existing materials, and achieves a high capacity and high efficiency sodium electro-negative electrode material.

CN119528112APending Publication Date: 2025-02-28SHENZHEN SANSO TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411726731.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode materials cannot be used under sodium ion battery systems, and the raw materials of hard carbon materials are high. How to use low-cost and stable and reliable materials to achieve the performance level of commercial hard carbon has become a research hotspot.

Method used

Asphalt is used as raw material, surface oxygen-containing functional groups are enhanced through surface oxidation, resin is added to form a cross-linked structure, and hard carbon structure is formed after high-temperature carbonization. There are a large number of irregular closed-cell structures, which improves the sodium storage performance of the material and reduces side reactions.

Benefits of technology

A high-performance sodium electro-anode material with a reversible capacity of more than 300mAh/g and an efficiency of more than 90% for the first time was obtained, which solved the problems of high cost and performance disadvantages and was market competitive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528112A_ABST
    Figure CN119528112A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a hard carbon sodium battery negative electrode material, and relates to a preparation method of a negative electrode material. The method comprises the following steps: 1, pre-oxidation treatment; 2, preparing an asphalt / binder mixture; 3, heat treatment; 4, rough grinding; 5, carbonizing; and 6, crushing. Asphalt which is low in cost and stable in supply is used as a raw material, surface oxygen-containing functional groups are enhanced through surface oxidation, then resin is added to serve as a binder to enable the asphalt to form a cross-linked structure, a large number of irregular closed-pore structures exist in a generated hard carbon structure through high-temperature carbonization, the sodium storage performance of the material is improved, meanwhile, the specific surface area is reduced, and the specific surface area is increased. Therefore, side reactions are reduced, the first efficiency is improved, and the high-performance sodium battery negative electrode material with the reversible capacity higher than 300mAh / g and the first efficiency higher than 90% is obtained. The hard carbon sodium battery negative electrode material can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a negative electrode material. Background Art

[0002] Currently, the primary negative electrode material for lithium-ion batteries is graphite, including both natural and artificial graphite. Compared to artificial graphite, natural graphite has higher specific capacity, higher compaction density, simpler processing, and lower production costs, but it suffers from significant disadvantages in terms of cycle performance and fast charging.

[0003] Sodium-ion battery is a rechargeable battery that uses sodium ions as charge carriers. Its working principle and structure are similar to those of lithium-ion batteries. The only difference is that lithium is replaced by sodium, which is in the same group in the periodic table and has similar chemical properties.

[0004] In recent years, with the rapid development of the new energy vehicle industry and large-scale electrochemical energy storage systems, global demand for lithium resources has continued to increase, and supply shortages have begun to emerge. Compared to lithium resources, my country has more abundant sodium resources, which can be mined and utilized on a large scale, breaking the supply and demand bottleneck of lithium resources.

[0005] Traditional graphite-based negative electrode materials for lithium batteries cannot be used in sodium-ion battery systems, so sodium-ion batteries need to be equipped with a completely new material system. The relatively mature negative electrode materials at present are hard carbon materials. At present, such materials use biomass (such as coconut shells, walnut shells), resins or cellulose as precursors. The capacity can usually reach more than 300mAh / g, and the first efficiency can reach more than 90%, but the cost of raw materials is relatively high. The other type, such as asphalt, anthracite, etc., are used as precursors. The porous carbon prepared is mostly soft carbon with low capacity, usually less than 280mAh / g, and the first efficiency is less than 86%. How to use low-cost, stable and reliable sources, and achieve material performance at the level of commercial hard carbon is currently a hot topic of research in this field. Summary of the Invention

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a hard carbon sodium negative electrode material.

[0007] The present invention has low usage costs and uses a stable supply of asphalt as raw material. Surface oxidation is adopted to enhance the surface oxygen-containing functional groups, and resin is added as a binder to form a cross-linked structure in the asphalt. High-temperature carbonization is then adopted to allow a large number of irregular closed-pore structures to be present in the generated hard carbon structure. While improving the sodium storage performance of the material, the specific surface area is reduced, thereby reducing the occurrence of side reactions and improving the initial efficiency, thereby obtaining a high-performance sodium negative electrode material with a reversible capacity of more than 300mAh / g and an initial efficiency of more than 90%.

[0008] A method for preparing a hard carbon sodium negative electrode material is specifically completed by the following steps:

[0009] Step 1: Pre-oxidation treatment:

[0010] Using an oxidant to oxidize the asphalt to obtain pre-oxidized asphalt;

[0011] Step 2: Prepare the asphalt / binder mixture:

[0012] Mixing the pre-oxidized asphalt with a binder and stirring for a period of time to obtain an asphalt / binder mixture;

[0013] Step 3: Heat treatment:

[0014] Under the protection of air or oxygen atmosphere, the asphalt / binder mixture is placed in a furnace for low-temperature heat treatment for a period of time to obtain a heat-treated material;

[0015] The temperature of the low-temperature heat treatment in step 3 is 200°C to 400°C, and the time of the low-temperature heat treatment is 60min to 180min;

[0016] Step 4: Coarse grinding:

[0017] coarsely grinding the heat-treated material to obtain a coarse particle material;

[0018] Step 5: Carbonization:

[0019] Under the protection of argon atmosphere, the coarse granular material is placed in a carbonization furnace and carbonized for a period of time to obtain a carbonized material;

[0020] The carbonization temperature in step 5 is 1100° C. to 1500° C., and the carbonization time is 60 min to 180 min.

[0021] Step 6: Crushing:

[0022] The carbonized material is crushed by air flow crushing equipment to obtain hard carbon sodium negative electrode material.

[0023] Principles and advantages of the present invention:

[0024] 1. The present invention uses a gaseous oxidant or a liquid oxidant to treat asphalt to increase the oxygen-containing functional groups on the asphalt surface. After the asphalt is mixed with the resin, a cross-linking reaction occurs during the low-temperature heat treatment process. The carbon chains of the asphalt are linked together through the "needle threading" of the resin to form an irregular pore structure. The oxidized asphalt has more surface functional groups, and the irregular pores formed are more abundant. During the subsequent high-temperature heat treatment, the material shrinks as a whole, and the irregular pores shrink to form a large number of closed pores. These closed pores are good sodium storage structures and are the key to increasing the material's capacity. At the same time, the closed pores do not increase the material's specific surface area, thereby avoiding more side reactions and improving the initial efficiency.

[0025] 2. The hard carbon sodium negative electrode material prepared by the present invention has both high capacity and high first efficiency. The hard carbon sodium negative electrode material prepared by the present invention has an initial discharge capacity of 324.88 mAh / g at a current density of 0.05C, and an initial efficiency of more than 94%. In contrast, the capacity of asphalt without oxidant treatment and plastic cross-linking is less than 230 mAh / g, and the initial efficiency is less than 75%.

[0026] 3. The raw materials for preparing hard carbon sodium negative electrode materials of the present invention are abundant and low in cost, the processing technology is simple, the key process only requires two steps of heating, no purification is required and no wastewater is generated, etc., which has obvious market competitiveness.

[0027] The invention can obtain a hard carbon sodium negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a capacity-voltage diagram of a CR2032 button battery assembled for the first time using the hard carbon sodium negative electrode material prepared in Example 1;

[0029] Figure 2 This is a capacity-voltage diagram of a CR2032 button battery assembled for the second time using the hard carbon sodium negative electrode material prepared in Example 1;

[0030] Figure 3 This is the test result of the hard carbon sodium negative electrode material prepared in Example 1;

[0031] Figure 4 This is an SEM image of the hard carbon sodium negative electrode material prepared in Example 1;

[0032] Figure 5 TEM image of the hard carbon sodium negative electrode material prepared in Example 1;

[0033] Figure 6 The infrared spectra of asphalt after and without pre-oxidation. DETAILED DESCRIPTION

[0034] Specific embodiment 1: This embodiment is a method for preparing a hard carbon sodium negative electrode material, which is specifically completed by the following steps:

[0035] Step 1: Pre-oxidation treatment:

[0036] Using an oxidant to oxidize the asphalt to obtain pre-oxidized asphalt;

[0037] Step 2: Prepare the asphalt / binder mixture:

[0038] Mixing the pre-oxidized asphalt with a binder and stirring for a period of time to obtain an asphalt / binder mixture;

[0039] Step 3: Heat treatment:

[0040] Under the protection of air or oxygen atmosphere, the asphalt / binder mixture is placed in a furnace for low-temperature heat treatment for a period of time to obtain a heat-treated material;

[0041] The temperature of the low-temperature heat treatment in step 3 is 200°C to 400°C, and the time of the low-temperature heat treatment is 60min to 180min;

[0042] Step 4: Coarse grinding:

[0043] coarsely grinding the heat-treated material to obtain a coarse particle material;

[0044] Step 5: Carbonization:

[0045] Under the protection of argon atmosphere, the coarse granular material is placed in a carbonization furnace and carbonized for a period of time to obtain a carbonized material;

[0046] The carbonization temperature in step 5 is 1100° C. to 1500° C., and the carbonization time is 60 min to 180 min.

[0047] Step 6: Crushing:

[0048] The carbonized material is crushed by air flow crushing equipment to obtain hard carbon sodium negative electrode material.

[0049] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the asphalt described in step 1 is medium-temperature asphalt or high-temperature asphalt with a softening point of 80° C. to 260° C. The other steps are the same as those in specific embodiment 1.

[0050] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the oxidant in step 1 is a gaseous oxidant or a liquid oxidant. The other steps are the same as those in specific embodiment 1 or 2.

[0051] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the gas oxidant in step 1 is oxygen or ozone; the concentration of oxygen is 150g / Nm 3 ~200g / Nm 3 , the concentration of ozone is 100g / Nm 3 ~200g / Nm 3 The other steps are the same as those in Specific Embodiments 1 to 3.

[0052] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the liquid oxidant described in step 1 is a hydrogen peroxide solution, a sodium dichromate solution, a nitric acid solution, and a potassium permanganate solution; the mass fraction of the hydrogen peroxide solution is 30% to 50%, the mass fraction of the sodium dichromate solution is 15% to 20%, the mass fraction of the potassium permanganate is 10% to 15%, and the mass fraction of the nitric acid solution is 8% to 12%.

[0053] The other steps are the same as those in Specific Embodiments 1 to 4.

[0054] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the oxidation treatment time in step 1 is 30 minutes to 60 minutes. The other steps are the same as those in specific embodiments 1 to 5.

[0055] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the binder in step 2 is polypropylene, polyethylene, or polyethylene terephthalate; and the particle size of the binder in step 2 is 300-400 mesh. The other steps are the same as specific embodiments 1 to 6.

[0056] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the mass ratio of the pre-oxidized asphalt to the binder in step 2 is 1:(1-10) and the stirring time in step 2 is 30 to 60 minutes. The other steps are the same as specific embodiments 1 to 7.

[0057] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the particle size of the coarse granular material in step 4 is 100 μm to 1000 μm. The other steps are the same as those of specific embodiments 1 to 8.

[0058] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the particle size of the hard carbon sodium negative electrode material in step 6 is ≤ 10 μm. The other steps are the same as specific embodiments 1 to 9.

[0059] The following examples are used to verify the beneficial effects of the present invention:

[0060] Example 1: A method for preparing a hard carbon sodium negative electrode material is specifically completed by the following steps:

[0061] Step 1: Pre-oxidation treatment:

[0062] Using an oxidant to oxidize the asphalt to obtain pre-oxidized asphalt;

[0063] The asphalt described in step 1 is medium-temperature asphalt with a softening point of 82°C;

[0064] The oxidant described in step 1 is a gaseous oxidant;

[0065] The gaseous oxidant described in step 1 is ozone;

[0066] The concentration of ozone is 150g / Nm 3 ;

[0067] The oxidation treatment time in step 1 is 40 min;

[0068] Step 2: Prepare the asphalt / binder mixture:

[0069] Mixing the pre-oxidized asphalt with a binder and stirring for a period of time to obtain an asphalt / binder mixture;

[0070] The binder described in step 2 is polyethylene terephthalate;

[0071] The particle size of the binder described in step 2 is 300 mesh;

[0072] The mass ratio of the asphalt after the pre-oxidation treatment described in step 2 to the binder is 1:8;

[0073] The stirring time in step 2 is 45 minutes;

[0074] Step 3: Heat treatment:

[0075] The asphalt / binder mixture is placed in a furnace under air and subjected to low-temperature heat treatment for a period of time to obtain a heat-treated material;

[0076] The temperature of the low-temperature heat treatment in step 3 is 300° C., and the time of the low-temperature heat treatment is 120 min;

[0077] Step 4: Coarse grinding:

[0078] Coarsely grinding the heat-treated material in step 3 to obtain a coarse particle material;

[0079] The particle size of the coarse particulate matter described in step 4 is 200 μm;

[0080] Step 5: Carbonization:

[0081] Under the protection of argon atmosphere, the coarse granular material is placed in a carbonization furnace and carbonized for a period of time to obtain a carbonized material;

[0082] The carbonization temperature in step 5 is 1300° C. and the carbonization time is 120 min.

[0083] Step 6: Crushing:

[0084] The carbonized material in step 5 is crushed by using air flow crushing equipment to obtain a hard carbon sodium negative electrode material;

[0085] The particle size of the hard carbon sodium negative electrode material described in step six is ​​≤10 μm.

[0086] Application Example 1: CR2032 button batteries were assembled using the hard carbon sodium negative electrode material prepared in Example 1, specifically by the following steps:

[0087] Step 1: 94 mg of the hard carbon sodium negative electrode material prepared in Example 1 was mixed evenly with 6 mg of sodium alginate, and then 0.5 mL of deionized water solvent was added and stirred evenly to prepare a slurry, which was then coated on a copper foil, dried, and cut to obtain a circular electrode sheet;

[0088] Step 2: Assemble a CR2032 button half-cell using the circular electrode sheet prepared in step 1 as the working electrode (positive electrode), Whatman GF / D as the separator, a metal sodium sheet as the counter electrode (negative electrode), and a 1M NaClO4 EC / DEC solution with 5% FEC added as the electrolyte;

[0089] The preparation method of the 1M NaClO4 EC / DEC solution with 5% FEC added described in step 2 is as follows: dissolving fluoroethylene carbonate (FEC) and NaClO4 in a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) to obtain a 1M NaClO4 EC / DEC solution with 5% FEC added, wherein the volume ratio of ethylene carbonate (EC) to diethyl carbonate (DEC) is 1:1, the mass fraction of fluoroethylene carbonate (FEC) is 5%, and the concentration of NaClO4 is 1 mol / L;

[0090] Step 3: Test the assembled CR2032 button battery using constant current charge and discharge technology in the test voltage range of 0.005~3V. The electrical performance is shown in Figure 1 and Figure 2 As shown;

[0091] The constant current charge and discharge procedure described in step 3 is: stand for 5 minutes - constant current discharge (0.05C) to 0.005V - stand for 5 minutes - constant current discharge (0.03C) to 0.005V - stand for 5 minutes - constant current charge (0.05C) to 3V - stand for 5 minutes (1C = 372mA / g).

[0092] Figure 1 and Figure 2 The capacity-voltage diagram of a CR2032 button cell assembled twice using the hard carbon sodium negative electrode material prepared in Example 1 is used to verify the authenticity of the electrochemical performance of the material.

[0093] Figure 1 This is a capacity-voltage diagram of a CR2032 button battery assembled for the first time using the hard carbon sodium negative electrode material prepared in Example 1;

[0094] Figure 2 This is a capacity-voltage diagram of a CR2032 button battery assembled for the second time using the hard carbon sodium negative electrode material prepared in Example 1;

[0095] from Figure 1 It can be seen that the CR2032 button battery assembled with the hard carbon sodium negative electrode material prepared in Example 1 has a first-cycle discharge capacity of 344.94 mAh / g, a first-cycle charge capacity of 324.88 mAh / g, and a first coulombic efficiency of 94.18%.

[0096] from Figure 2 It can be seen that the first cycle discharge capacity of the CR2032 button battery assembled with the hard carbon sodium negative electrode material prepared in Example 1 is 334.29 mAh / g, the first cycle charge capacity is 316.30 mAh / g, and the first coulombic efficiency is 94.62%. Figure 1 The difference is not big, and the data is reliable. It can be considered that the hard carbon sodium negative electrode material prepared in Example 1 has a higher first coulombic efficiency and relatively excellent first charge and discharge performance.

[0097] Figure 3 This is the test result of the hard carbon sodium negative electrode material prepared in Example 1;

[0098] Figure 4 This is an SEM image of the hard carbon sodium negative electrode material prepared in Example 1;

[0099] Figure 5 TEM image of the hard carbon sodium negative electrode material prepared in Example 1;

[0100] Figure 6 These are the infrared spectra of asphalt after and without pre-oxidation.

Claims

1. A method for preparing a hard carbon sodium negative electrode material, characterized in that The preparation method is specifically completed according to the following steps: Step 1: Pre-oxidation treatment: Using an oxidant to oxidize the asphalt to obtain pre-oxidized asphalt; Step 2: Prepare the asphalt / binder mixture: The pre-oxidized asphalt is mixed with a binder and stirred for a period of time to obtain an asphalt / binder mixture; Step 3: Heat treatment: Under the protection of air or oxygen atmosphere, the asphalt / binder mixture is placed in a furnace for low-temperature heat treatment for a period of time to obtain a heat-treated substance; The temperature of the low temperature heat treatment in step 3 is 200°C to 400°C, and the time of the low temperature heat treatment is 60min to 180min; Step 4: Coarse grinding: coarsely grinding the heat-treated material to obtain a coarse particle material; Step 5: Carbonization: Under the protection of argon atmosphere, the coarse granular material is put into the carbonization furnace and carbonized for a period of time to obtain the carbonized material; The carbonization temperature in step 5 is 1100° C. to 1500° C., and the carbonization time is 60 min to 180 min. Step 6: Crushing: The carbonized material is crushed by air flow crushing equipment to obtain hard carbon sodium negative electrode material.

2. The method for preparing a hard carbon sodium negative electrode material according to claim 1, characterized in that The asphalt described in step 1 is medium-temperature asphalt or high-temperature asphalt, and the softening point is 80°C to 260°C.

3. The method for preparing a hard carbon sodium negative electrode material according to claim 1, characterized in that The oxidant described in step 1 is a gaseous oxidant or a liquid oxidant.

4. The method for preparing a hard carbon sodium negative electrode material according to claim 3, characterized in that The gaseous oxidant in step 1 is oxygen or ozone; the concentration of oxygen is 150g / Nm 3 ~200g / Nm 3 , the concentration of ozone is 100g / Nm 3 ~200g / Nm 3 .

5. The method for preparing a hard carbon sodium negative electrode material according to claim 1, characterized in that The liquid oxidant described in step 1 is hydrogen peroxide solution, sodium dichromate solution, nitric acid solution, and potassium permanganate solution; the mass fraction of the hydrogen peroxide solution is 30% to 50%, the mass fraction of the sodium dichromate solution is 15% to 20%, the mass fraction of the potassium permanganate is 10% to 15%, and the mass fraction of the nitric acid solution is 8% to 12%.

6. The method for preparing a hard carbon sodium negative electrode material according to claim 5, characterized in that The oxidation treatment time in step 1 is 30 min to 60 min.

7. The method for preparing a hard carbon sodium negative electrode material according to claim 1, characterized in that The binder described in step 2 is polypropylene, polyethylene or polyethylene terephthalate; the particle size of the binder described in step 2 is 300 mesh to 400 mesh.

8. The method for preparing a hard carbon sodium negative electrode material according to claim 1, characterized in that The mass ratio of the pre-oxidized asphalt to the binder in step 2 is 1:(1-10); the stirring time in step 2 is 30 min-60 min.

9. The method for preparing a hard carbon sodium negative electrode material according to claim 1, characterized in that The particle size of the coarse granular material described in step 4 is 100 μm to 1000 μm.

10. The method for preparing a hard carbon sodium negative electrode material according to claim 1, characterized in that The particle size of the hard carbon sodium negative electrode material described in step six is ​​≤10 μm.

Citation Information

Patent Citations

  • Performance improvement method and application of sodium-ion battery carbon-based negative electrode material

    CN113526489A

  • Hard carbon negative electrode material prepared by pitch-based oxidation method and preparation method and application thereof

    CN115259135A

  • Asphalt-based hard carbon negative electrode material, preparation method and sodium ion battery

    CN115611264A

  • Heterojunction carbon material, preparation method and application thereof

    CN116947014A

Cited By

  • Sodium-ion battery hard carbon material and preparation method thereof

    CN122380342A